The Modified Arch Landing Areas Nomenclature identifies hostile zones for endograft deployment: a confirmatory biomechanical study in patients treated by thoracic endovascular aortic repair. (7th December 2018) - Marrocco-Trischitta, Massimiliano M; Romarowski, Rodrigo M; de Beaufort, Hector W; Conti, Michele; Vitale, Renato; Secchi, Francesco; Auricchio, Ferdinando; Trimarchi, Santi
Abstract: OBJECTIVES: Our goal was to confirm whether the Modified Arch Landing Areas Nomenclature (MALAN) for thoracic endovascular aortic repair, in which each landing area is described by indicating both the proximal landing zone (PLZ) and the type of arch (e.g. 0/I), identifies unfavourable landing zones for endograft deployment in diseased aortas. METHODS: Preoperative computed tomography angiography scans of 10 patients scheduled for thoracic endovascular aortic repair for aneurysm or penetrating ulcer of the arch and with a potential hostile PLZ were reviewed. Five had proximal deployment planned in MALAN area 3/III and 5, in MALAN area 2/III. The angulation of each PLZ was calculated. Computational fluid dynamics modelling was used to compute magnitude and orientation of pulsatile displacement forces in each PLZ. Normalized values based on PLZ areas (i.e. equivalent surface traction) were calculated. Results were compared to those obtained in healthy controls stratified by the MALAN. RESULTS: Angulation was severe (>60°) in MALAN areas 3/III and 2/III, which was consistent with the findings obtained in healthy controls. Increased magnitude ( P = 0.021) and unfavourable orientation (i.e. orthogonal to the longitudinal aortic axis) of equivalent surface traction ( P = 0.011) was also found in these areas compared to the adjacent ones, following the same pattern seen in the controls. Adverse events related to proximal endograft performance were reported in 3/10 cases. CONCLUSIONS: This study confirms in diseased aortas initial proof-of-concept findings on the predictive value of the MALAN to identify landing areas with a geometric and haemodynamic environment hostile for thoracic endovascular aortic repair. These adverse biomechanical features may entail an increased risk of dismal endograft performance.